Investigations of a four-stroke flexible valve timings system - Muhammad Haziq Adham, Rosli (2021)
Variable valve timing (VVT) technology has been successful in enhancing internal combustion (IC) engine performance. VVT offers additional control on engine breathing so that the engine operating conditions may be tailored more precisely; hence, output and performance are amplified. VVT is one of the best ways to be implemented as it is cheap at cost and feasible without adding too much weight to the car. However, in VVT, there is a challenge within in order to provide the optimum valve lift profile. In this research, an investigation of a four-stroke spark ignition engine using a numerical tool is presented. The objectives carried in this research is, to investigate the engine performance characteristic of a four-stroke spark-ignition engine using a numerical tool by using real time data from benchwork experiment, to investigate the intake and exhaust performance characteristics for variable valve timing through optimization technique of improving engine performance and efficiency, to improve engine performance of flexible valve timing (FVT) strategies in tool using statistical analysis and design of experiment. The primary goal is to show engine performance boosting could be achieved by the implementation of FVT strategies. A numerical baseline model was developed using numerical simulation tool based on a 65cc four-stroke gasoline engine. The flow coefficient values of intake and exhaust ports were obtained from flow bench experiments with the highest value of 0.397 and 0.441 respectively. A simulation assessment has been conducted using the real specifications and parameters of an actual engine. The baseline model was validated against manufacturer specifications. The engine performances of the baseline model were investigated. This model undergone performance tuning to obtain the optimum power and torque curves for the whole engine speed range. Performance optimization was conducted through design of experiments (DOE) using full factorial matrix with the target of boosting the performance of the baseline model. This was obtained through the variation of intake and exhaust valves timing as well as maximum lift using a full factorial experiment with three levels. The DOE experiments have identified several optimum FVT profiles. The result has shown an increase of up to 11.49% in brake power with maximum 2.52kW produced compared to the baseline model with maximum value of 2.3kW. Volumetric efficiency is improved resulting in BMEP amplification with more than 10%. Fuel consumption and gas emissions rate are also improved significantly using the FVT application. Few FVT strategies have been identified as beneficial variables to boost engine performance. EIVC and EEVC are advantageous at lower engine speed, while LIVC, EIVO, and LEVC are advantageous at higher speed. LEVO and higher intake valve lift are beneficial at all speeds. LIVO and EEVO show no positive impact on engine performance. In conclusion, this study has shown high potential of FVT strategies which can improve engine performance over the whole range of engine speeds.